PENGARUH HARGA DIRI TERHADAP KECENDERUNGAN BODY DYSMORPHIC DISORDER PADA REMAJA - Fionna Gracia; Zarina Akbar (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2019)
This study aims to determine the influence of self-esteem towards body dysmorphic disorder tendency in adolescence. The study was conducted with quantitative method towards 112 adolescents within 15- 17 range of age. Body dysmorphic disorder tendency was measured using an instrument of which adapted from Katherine Phillips theories. Self-esteem was measured using Rosenberg Self-esteem Scale (RSES) Statistical analysis was conducted to test the hypothesis using one predictor regression analysis. The result shown F= 27,735; p = 0,000<0,005 Thus, there is influence between self-esteem towards body dysmorphic disorder tendency in adolescense. Effective contribution of self-esteem to the tendency of body dysmorphic disorder is 20.1%